Bringing Earthbags to the People – A New, Democratic Approach to Sustainable Building - Zemskova, Kateryna; Belofsky, Nathan (Consilience, 2018)
Earthbag technology builds safe, appealing, and cost-effective structures out of ordinary soil. Stronger, cheaper, and less harmful to the environment than conventional building techniques like brick and cement, Earthbag technology is generally considered the most promising of sustainable building techniques. But despite widespread support among environmental groups and eco-builders, this method is shunned by governments and remains virtually unknown to everyday building professionals and the public. This paradigm, however, is changing in Nepal, where a catastrophic 2015 earthquake flattened much of the housing stock. Good Earth Nepal, a non-profit organization, has pioneered a three-pronged approach designed to overcome resistance to sustainable building and to, for the first time, make Earthbag technology accessible to the masses.